An Inquiry into Renaissance Art and Literature - Yao, Zijing (Transactions on Social Science, Education and Humanities Research, 2024)
The Renaissance (14th to 17th centuries) is an important period in European history, known as the Golden Age of art and literature. This period began in Italy and gradually spread to other parts of Europe. The Renaissance was a revolt against the feudal system and religious dogma of the Middle Ages, and a revolution in thought and culture. Humanism, the core ideology of the period, emphasized human values and rationality and encouraged individuals to pursue knowledge and self-realization. At the same time, art as well as literature began to be produced in great numbers, taking on a completely different appearance from that which existed before the beginning of the movement. The art and literature of this period reflected a major shift in human thought from the religious confinement of the Middle Ages to a focus on humanism and personal values. This paper examines the major art forms of the Renaissance and their representatives and analyzes the development of literature and its influence at the time. Through an in-depth analysis of Renaissance art and literature, it reveals the importance of the period in shaping modern European culture and thought..